Land Resources Appraisal of Bnagladesh for Agricultural Development Report-5 Land Resources Volume-11-16 Land Resources Map and Legend Parts of Rangamati-Chittagong-Bandarban (Rome : UNDP and FAO, 1988)
Environment Management
09\05\02
Keywords: Agricultural Development; Land; Bangladesh